Full-length transcriptome provides insights into the molecular regulation of seed spike number in Agropyron mongolicum - Guo, Meiying; Wei, Yaqin; Liu, Xiqiang; Huang, Xintian; Liu, Yaling; Zhao, Yan (Frontiers in Plant Science, 2025)
Agropyron mongolicum is a xerophytic perennial grass with good palatability and nutritional value, predominantly distributed in sandy, arid regions and desert steppes of northwest China. However, its low biomass and limited seed yield pose significant challenges for large-scale cultivation and forage production. To date, there have been limited genomic or transcriptomic studies on A. mongolicum, particularly regarding the molecular genetic mechanisms underlying yield-related traits. In this study, we employed an integrated transcriptomic approach combining long-read sequencing (PacBio Iso-Seq) and short-read sequencing (Illumina RNA-seq) to generate a comprehensive full-length transcriptome from four tissues—leaves, stems, young spikes, and mature spikes. Transcriptomic comparisons between multi-spike and few-spike germplasms were performed to identify candidate genes involved in the regulation of spike number. A total of 762,116 full-length transcripts were generated, among which 214,500 were successfully annotated. We identified 185,424 unique genes, including 91,514 differentially expressed genes (DEGs). Functional enrichment analysis revealed 43 DEGs associated with the protein processing pathway in the endoplasmic reticulum. Notably, 8 DEGs were specifically expressed in young spikes and mature spikes of the contrasting spike-number germplasms, suggesting their potential role in spike number regulation. This study provides a high-quality transcriptomic resource and identifies candidate genes that may facilitate molecular breeding for enhanced seed yield in A. mongolicum.